Về pha nghịch đảo kiến tạo Miocen muộn ở phần Tây Bắc Bồn trũng sông Hồng - Việt, Lê Triều; Thắng, Trần Văn (Vietnam Journal of Earth Sciences, 2008)
About the Late Miocene tectonic inversion phase in Northwestern part of Bac Bo gulf